The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/07908318.2016.1154068
|View full text |Cite
|
Sign up to set email alerts
|

Urban vs. rural CLIL: an analysis of input-related variables, motivation and language attainment

Abstract: The present article carries out an in-depth analysis of the differences in motivation, input-related variables and linguistic attainment of the students at two content and language integrated learning (CLIL) schools operating within the same institutional and educational context, the Spanish region of Extremadura, and differing only in terms of the social milieu: rural vs. urban. The results show that the CLIL learners in the urban school (n = 27) had started earlier, had had greater formal support outside sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
3
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 44 publications
1
18
3
5
Order By: Relevance
“…Likewise, and in line with the hypothesis raised, Leyton et al [71], in a sample between the ages of 18 and 65, found higher values in the most self-determined forms of motivation and reasons for practice in rural areas, as opposed to urban areas. However, unlike in the present study, Alejo et al [72] found no differences in the motivational profile of students in urban and rural schools regarding foreign language learning, although the former showed lower levels of anxiety with respect to the latter.…”
Section: Discussioncontrasting
confidence: 99%
“…Likewise, and in line with the hypothesis raised, Leyton et al [71], in a sample between the ages of 18 and 65, found higher values in the most self-determined forms of motivation and reasons for practice in rural areas, as opposed to urban areas. However, unlike in the present study, Alejo et al [72] found no differences in the motivational profile of students in urban and rural schools regarding foreign language learning, although the former showed lower levels of anxiety with respect to the latter.…”
Section: Discussioncontrasting
confidence: 99%
“…Estudios como el presente son una valiosa fuente de información que arrojan luz a un tema tan controvertido como los efectos de la enseñanza bilingüe en el alumnado (Ardila, 2012;Barrios, 2015;Bravo-Torija, et al 2016;Bruton, 2015;Costa, 2018;Núñez, 2007). A pesar de que existe un elevado número de investigaciones destinadas a comprobar la efectividad de los programas bilingües en la mejora de la competencia lingüística en la LE y en la adquisición de conocimientos relativos a las DNL impartidas en la LE (Anghel, et al, 2016(Anghel, et al, , 2016Esparza y Belmonte, 2020;Fernández-Sanjurjo, et al, 2017;Gallardo y Gómez, 2017;Ródenas-Ríos, 2018), se percibe un descenso en las investigaciones destinadas a evaluar la influencia de los programas bilingües en la actitud del alumnado hacia el idioma inglés y hacia las ciencias, la cual es una de las asignaturas incluidas en las DNL (Alejo y Piquer-Píriz, 2016;Calderón y Morilla, 2018;Lancaster, 2018;Paz-Albo, et al, 2018;Pladevall-Ballester;.…”
Section: Discusión Y Conclusionesunclassified
“…En este punto consideramos necesario señalar que, como sucede en toda investigación, el presente trabajo presenta algunas limitaciones que han podido condicionar nuestro estudio. Dada la importancia de los contextos sociales en el proceso de enseñanza y aprendizaje del idioma (Alejo y Piquer-Píriz, 2016;Martínez, 2020), consideramos que la falta de información relativa a la situación económica y sociocultural de las familias supone una de las principales limitaciones del estudio. Además, el nivel de fiabilidad del cuestionario, así como el uso de una escala dicotómica en lugar de una escala Likert nos ha impedido realizar un análisis en profundidad los matices de las respuestas o conocer el grado de conformidad de los sujetos en relación a los enunciados planteados.…”
Section: Discusión Y Conclusionesunclassified
“…In order to implement the bilingual sections project efficiently, the educational authorities of the region have established some regulations (Junta de Extremadura, 2011, 2013), such as establishing the foreign languages that can be used (English, French or Portuguese), the number of content areas, the roles of the teachers, and demanding some requirements of the teachers regarding their methodology and language knowledge (for more detailed information, see Alejo & Piquer-Píriz, 2010, 2016a, 2016b.…”
Section: Clil In Extremaduramentioning
confidence: 99%